2013
DOI: 10.1002/qre.1598
|View full text |Cite
|
Sign up to set email alerts
|

On Enhanced Interquartile Range Charting for Process Dispersion

Abstract: A careful monitoring of process dispersion is necessary to get optimum output from any process. Control charts are very important process monitoring tools of Statistical Process Control toolkit. Interquartile range (IQR) is a famous dispersion measure that is used to monitor process dispersion in quality control literature. In this study, a set of auxiliary information-based Shewhart-type IQR charts are proposed for efficient monitoring of process dispersion under bivariate normal, t and gamma distributed proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Recently, Riaz has proposed improved Shewhart‐type charts using AIB location estimators. For more interesting works on the AIB charts, we refer to Haq and Khoo, Abbasi and Riaz, Arshad et al ., Riaz et al ., Riaz, and Riaz et al ., to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Riaz has proposed improved Shewhart‐type charts using AIB location estimators. For more interesting works on the AIB charts, we refer to Haq and Khoo, Abbasi and Riaz, Arshad et al ., Riaz et al ., Riaz, and Riaz et al ., to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that the performance of R and S charts is highly affected by the non‐normal cases, while IQR chart performs better than R and S charts. The dispersion parameter monitoring by using IQR has been discussed by various authors in literature, for example 19,31–34 . For the efficient monitoring of the dispersion parameter, Riaz 33 proposed the Shewhart charting structure through the use of a set of additional information IQR control charts under normal, t , and gamma‐distributed processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al 19 continued Riaz's 33 work and proposed EWMA charting structure by using auxiliary information‐based IQR charts and compared the efficiency of the proposed charts with usual R and S charts under both contaminated and uncontaminated scenarios. Consequently, as per our best knowledge, there has been no research in introducing the concept of auxiliary information‐based IQR control charts into the CUSUM charting structure for dispersion monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al 24 investigated a set of variance control charts based on one and two auxiliary variables. Riaz 25 proposed a set of Shewhart‐type interquartile range dispersion charts using supplemental information for monitoring process dispersion. Haq et al 26 proposed a synthetic exponentially weighted moving average control chart for monitoring process dispersion.…”
Section: Introductionmentioning
confidence: 99%